Book Launch and Scientific Workshop "Follow Your Heart. The School for Multipotentialites" - Poto, Margherita Paola; Murray, Emily Margaret; Russo, Valentina (Septentrio Reports, 2023)
The overall aim of this report is to document the experience gained during the book launch and co-created, experiential workshop on the book "Follow Your Heart: the school for multipotentialites." Reflecting on the dynamic process triggered by the research gathered and further developed throughout the book helps to create ideas and practices toward transformative change in research and education. The authors planned three book launches, structured as innovative academic presentations combined with creativity workshops that follow some of the suggested activities that were specifically created for the book. The first book launch was held in Shepton Mallet, Somerset, UK, and hosted by the educational farm The Good Life Projects, coordinated by Craig Stevens, on February 18, 2023. The proceeds from the book launch (collected through book sales) were donated to Windsor Hill Wood, a place of refuge and community in the local area that helps people heal, grow, and rebuild their lives while taking care of nature and encouraging sustainable livelihoods. Windsor Hill Wood as a community and philosophy closely align with the authors' beliefs and the main concepts of Follow Your Heart, which made the overall impact of the first book launch exceptionally more meaningful. This report is designed to share the key insights from the event and promote further discussion within the field of emotional and ecological education, in line with the project ECO_CARE. The report is accordingly divided into the following sections: 1. Introduction; 2. Follow Your Heart: audience, vision and development; 3. Ways forward; 4. Reference list.